Comparison analysis between the components of vernacular and modern architectures for sustainable housing in Niger State - Dada, Abubakar Dauda; Alibaba, Halil Zafer (Institute of Physics, 2023)
Modern architecture has its roots in the vernacular type. Globally, every cultural group has its own form of vernacular architecture, though the approach may vary from region to region and also among the individuals. The traditional and modern architectural styles in Minna Niger State, Nigeria are examined in this paper since these styles possess distinct climatic, economic, and socio-cultural practices. A typical vernacular architecture was sited at Tudun Fulani Extension whereas a typical modern architecture was sited at GidanMatasa. The study examined the buildings in terms of physical features, thermal comfort and cost analysis. EnergyPlus, a simulation program, was used in this study to assess and forecast the thermal comfort. To affirm, local construction materials were used to meet the housing demands without harming the environment. The study outcomes found that the traditional housing units outperformed the modern ones by a wide margin. The findings of the study revealed the following features as part of vernacular architecture such as the presence of a courtyard, vegetation, connection to nature and construction using natural materials. On the other hand, the modern architecture does not have any courtyards, inadequate vegetation and isolation from the nature. It is also constructed using the imported building materials, although the modern architecture enables the windows to be of large size. The findings also disclose that the vernacular architecture provides more thermal comfort than the modern architecture since the latter has a heavy heating load density i.e., 9,571 (Watt). This value is 50 percent more than the peak heating load of the traditional architectural structure i.e., 2,109 (Watt). Finally, the study was able to ascertain the high-cost implication of the modern architecture compared to vernacular architecture. Furthermore, the study also proved that the vernacular housing units are much better than the modern ones in terms of thermal comfort, usage of cost-effective and natural materials and the building's thermal properties. The researcher recommends that the components of both vernacular and modern architecture must be properly integrated for the development of the sustainable homes in Northern Nigeria. © Published under licence by IOP Publishing Ltd.
1st International Conference on Design Innovations and Management for Sustainable Environment, ICDIMSE 2022 -- 2022-03-15 through 2022-03-16 -- Virtual, Online -- 190930
Keywords: Energyplus; Modern Architecture; Niger; Nigeria; Vernacular Architecture